PERAN DUKUNGAN PSIKOSOSIAL PERAWAT DALAM MENURUNKAN DEPRESI POSTPARTUM: STUDI KASUS DI RUANGAN JADE RSUD SLAMET GARUT - Alifia Zalfa; Ida Maryati; Sukmawati Sukmawati (SINERGI : Jurnal Riset Ilmiah, 2026)
Postpartum mothers often experience emotional changes characterized by unexplained crying, irritability, and excessive anxiety, commonly known as postpartum depression. If left untreated, postpartum depression may progress to major depressive disorder, reduce a mother's ability to care for her newborn, hinder mother–infant bonding, and increase the risk of developmental and psychosocial problems in the child later in life. Therefore, early psychosocial support is essential to help mothers adapt emotionally and prevent long-term consequences. This case study aims to explore the role of psychosocial support provided by nurses in reducing postpartum depression. Methods: This study employed a descriptive case study approach conducted in the Jade Ward of RSUD dr. Slamet Garut. The subject was Mrs. R, a 24-year-old mother on days 18, 19, and 20 post–cesarean section. Data were collected through interviews, observations, and medical record reviews. The Edinburgh Postnatal Depression Scale (EPDS) was used to assess depression levels before and after the intervention. The main intervention consisted of psychosocial support delivered over three days through therapeutic communication, emotional exploration, relaxation exercises, and facilitation of family support. Results: The EPDS score decreased from 15 to 10 after three days of intervention. Subjectively, the mother reported feeling calmer, began showing interest in caring for her baby, and became more open in communicating with her family. Conclusion: Psychosocial support effectively reduced postpartum depression by enhancing emotional well-being and perceived social support. Nurses are expected to play roles as educators, counselors, and facilitators of family involvement in supporting the psychological adaptation of postpartum mothers.